Market design in the Smart Grid - Greve, T. (Smart Grid Handbook, 2016)
A successful market depends on the design and the mechanism used. However, first it needs to be asked – what is the market? How does it work? How does it fail? How can it be fixed when it is broken? One can pose the same questions in the area of electricity and smart grids. The goal is efficient trade. Efficient pricing and allocation are the ingredients necessary to achieve this goal. The right market design can answer the questions and can ensure the desired outcome. This chapter examines the possible transformation of design. It starts with an analysis of the market designs in use today, current changes in designs as a result of smart grids and a potential market design for the future. Auctions are and have been the main market design mechanism in use. The focus therefore is on the necessary framework for using auctions. Further, it shows that the trend is moving away from the wholesale market towards the retail market to include active consumers with “smart” behavior. It suggests that there will be a move away from the use of capacity and energy markets and back towards an “energy only” market. These will have significant impacts on future electricity market design. Finally, this chapter presents a solution that could incorporate these future changes.